A cooperative game approach for coordinating multi-microgrid operation within distribution systems. (15th July 2018) - Du, Yan; Wang, Zhiwei; Liu, Guangyi; Chen, Xi; Yuan, Haoyu; Wei, Yanli; Li, Fangxing
Highlights: A coalitional operation model for multiple microgrids to achieve global optimum. A cost allocation method from cooperative game theory to achieve local optimum. A linearized optimal power flow with voltage constraints to realize cooperation. The economy benefits of multi-microgrid cooperation are simulated and analyzed. Abstract: This paper focuses on simulating the potential cooperative behaviors of multiple grid-connected microgrids to achieve higher energy efficiency and operation economy. Motivated by the cooperative game theory, a group of individual microgrids is treated as one grand coalition with the aim of minimizing the total operation cost. Next, given that each microgrid operator is an independent and autonomous entity with the aim of maximum self-interest, a cost allocation method based on the concept of core in the cooperative game is implemented to ensure a fair cost share among microgrid coalition members, which guarantees the economic stability of the coalition. Considering the combinatorial explosive characteristic of the cost allocation problem, Benders Decomposition (BD) algorithm is applied to locate the core solution with computational efficiency. In addition, since microgrid coalition is formed at the distribution system level, network losses is not negligible. After considering network losses, the coalition operation model of multi-microgrid becomes an optimal power flow problem. A linearized optimal power flow for distribution (LOPF-D) model is applied instead of the conventional ACOPF model to reduce computation burden, meanwhile maintaining adequate accuracy. Case studies on standard IEEE systems demonstrate the advantages of multi-microgrid cooperation and the robustness of the formulated grand coalition. In addition, comparisons with the conventional ACOPF model verifies the high performance of the proposed LOPF-D model.